Significance of Haptic and Virtual Reality Simulation (VRS) in the Dental Education: A Review of Literature - Eisha Imran (MDPI AG, 2021)
The significance of haptic and virtual reality (VR) has been acknowledged by eminent dental professionals and has transformed dental teaching in the modern dental world. With this novel technological concept, students can interact with digital simulation on the screen and learn treatment skills before transferring them to real situations. This is helpful for gaining skills confidence, revising exercises again and again without the waste of materials, and for student assessment controlled by a teacher or tutor. It is a promising technology to enhance dental education for the new era of post COVID-19 practice due to noncontact patient training environments. It can create a safe learning environment for the teacher and learner or participant. The prospect of this literature review is to highlight the significance and clinical applications of virtual reality and simulations in undergraduate dental education.